The Effect of ICARE Learning Model on Junior High School Students' Mathematical Problem-Solving Ability - Djailani, Sri Rahmatia S.; Majid; Usman, Kartin (IKIP Siliwangi, 2026)
The mathematical problem-solving ability of junior high school students is still considered low, as evidenced by the low learning outcomes among seventh-grade students at SMP Negeri 1 Suwawa. To enhance this ability, an innovative learning model is required. One such model is ICARE, which is believed to encourage active student engagement and foster a deeper understanding of mathematical concepts. This study aims to determine the differences between the ICARE learning model and the conventional learning model on the mathematical problem-solving abilities of seventh-grade students at SMP Negeri 1 Suwawa. The research was conducted from May to June during the even semester of the 2024/2025 academic year. The research method employed in this study was an experimental method involving two classes, namely the experimental class and the control class. Simple random sampling was used to select the samples. The research design utilized was a Post-test Only Control Group Design. The data were collected through a written post-test. The results of the study, based on hypothesis testing using a t-test, showed that the obtained tcount​ = 3.050, while the critical ttable = 2.007 at a significance level of 0.05. Since tcount​> ttable the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted. Therefore, it can be concluded that the mathematical problem-solving ability of students taught using the ICARE learning model is higher than that of students taught using the conventional learning model.